Signatures of Transient Overvoltages in Low Voltage Power Systems in Tea Factories and Their Implications on Insulation Deterioration and Allied Power Quality Issues - Earl A. R. L. Pannila; Mahesh Edirisinghe (Journal of Electrical and Computer Engineering)
Electrical equipment and supply cables demand a better quality of supply, with the recent advancements in integrated sensitive solid-state controls. Divergently, proliferated heavy inductive motors and some performance additions based on power electronics have introduced power quality issues to the network. Thus, this study mainly investigates the impact of switching transients generated by electromechanical machines in industrial power systems on insulation deterioration while taking transient overvoltages due to capacitor bank switching also to support. Transients with a high rate of rise are likely to catalyze the degradation of the insulation quality and break down the insulating material through ionization. These steeply passing overvoltage stresses let partial discharges ensue, which can attack the insulation over long service. To unveil this danger, 314 common-mode transient waveforms were measured in the electrical machines of five tea factories in Sri Lanka, in a 50 ms measurement window, taken in 55 measuring attempts. Most of the transients observed are in the form of a damped oscillatory waveform tailed by fast exponential collapse. That correlates to insulation degradation having a very steep rise as 30.04 V/ns, the highest at the withering section. When machines are heavily loaded, situations tend to generate transients with high amplitudes. There were transient bursts that spread as 426.3 ms, while 14 ns fast rise times were recorded from withering motors. Unlike electrical resonance and power-frequency overvoltages, electromagnetic switching transients last even less than 100 ms. To underline this, an analysis of the frequency domain of transients was also presented, which proves high density of high-frequency components reaching 107 kHz range. Accepting the fact that frequency and amplitude are always under the influences of innumerable dynamics, the observational evidence of the study endorses that electrical stress built by the transient nature of the factories reduces the life expectancy of electrical insulation.